Modelo de conductancia hidráulica de la dentina humana ex vivo - Hevia, Javier; Fresno, Consuelo; Martin, Javier; Moncada, G; Letelier, Claudia; Oliveira Júnior, Osmir Batista de [UNESP]; Fernández, Eduardo [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2013)
The main objective of this work was to mount and test an experimental model to measure the hydraulic conductance of ex vivo dentin. Seventeen healthy third molars, with indication of extraction of healthy donors aged between 15 and 30 years were obtained by informed consent. After cleaning them, disinfecting them, including them in resin epoxy and cutting them, there were 17 samples of dentin, corresponding to a disk of resin with a coronal section of tooth showing the dentin exposed on both sides of it. Three machines to measure the hydraulic conductance of the dentin were assembled according to the description of the model of Pashley. Samples were installed in a Chamber of diffusion, connected by using silicone tubes to a graduated transfer pipette and a 20cm water column. Through the displacement of a bubble of water in the inside of the pipette, the hydraulic conductance of each sample was measured 3 times on the 14th, 21st, 28th and 35th day post extraction. The data were tabulated and analyzed statistically. There is no SS difference in the rate of flow of a measured sample in the three machines (p=0.5937). There is no SS difference in measurements of the hydraulic conductance of 13 samples of human dentin measured in days 14, 21, 28 and 35 postextraction (p=0.0704). It is possible to mount an experimental model to study the hydraulic conductance of dentin ex vivo, based on the model of Pashley. The model seems to be reliable, but more research is needed in order to validate its reliability.

El objetivo principal de este trabajo fue montar y probar un modelo experimental para medir la conductancia hidráulica de la dentina ex vivo. Diecisiete terceros molares sanos, con indicación de exodoncia, de donantes sanos de edades entre 15 y 30 anos fueron obtenidos mediante consentimiento informado. Luego de limpiarlos, desinfectarlos, incluirlos en resina epóxica y cortarlos se obtuvieron 17 muestras de dentina, correspondiente a un disco de resina con un corte coronal de diente que presenta dentina expuesta en ambas caras de éste. Tres equipos para medir la conductancia hidráulica de la dentina fueron armados siguiendo la descripción del modelo de Pashley. Las muestras fueron instaladas en una cámara de difusión, conectada mediante tubos de silicona a una pipeta graduada y una columna de agua de 20cm. Mediante el desplazamiento de una burbuja de agua al interior de la pipeta, se midió la conductancia hidráulica de cada muestra, 3 veces los días 14, 21, 28 y 35 postextracción. Los datos fueron tabulados y analizados estadísticamente. No existe diferencia en la tasa de flujo de una muestra medida en los tres equipos (p=0.5937). No existe diferencia en las mediciones de la conductancia hidráulica de 13 muestras de dentina humana medida en los días 14, 21, 28 y 35 postextracción (p=0.0704). Es posible montar un modelo experimental para estudiar la conductancia hidráulica de la dentina ex vivo, basado en el modelo de Pashley y col. El modelo pareciera ser confiable, pero es necesaria más investigación para poder validar su confiabilidad.
Hydraulic conductance model of ex vivo human dentin
Keywords: Dentin; Conductance; Diffusion; Dentina; Conductancia; Difusión